Defect‐Free Nanocrystals: Impurity‐Induced First‐Order Phase Transitions in Highly Crystalline V2O3 Nanocrystals (Adv. Mater. Interfaces 12/2015). Issue 12 (19th August 2015) - Ishiwata, Yoichi; Takahashi, Eiko; Akashi, Kenta; Imamura, Masaki; Azuma, Junpei; Takahashi, Kazutoshi; Kamada, Masao; Ishii, Hirofumi; Liao, Yen‐Fa; Tezuka, Yasuhisa; Inagaki, Yuji; Kawae, Tatsuya; et al.
<x xml:space="preserve">Abstract</x> In article 1500132, Y. Ishiwata and co‐workers demonstrate nanoscale first‐order phase transitions (metal–insulator transition, antiferromagnetic transition, and structural phase transition) in highly crystalline V2O3 nanocrystals doped with Cr or Ti impurities of more than a certain amount. This observation shows that impurity doping is an efficient method to cause a phase transition that was originally suppressed in high‐quality nanoscale materials.